2022
DOI: 10.1002/adfm.202111698
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Antibiotic Hydrogel that Scavenges Proinflammatory Factors for the Treatment of Severe Abdominal Trauma

Abstract: Bacterial infection and excessive inflammation following abdominal injury can cause life-threatening complications that lead to multiple organ failure and death. Removing bacteria and proinflammatory factors-which are predominantly negatively charged-from the wound site with a cationic, antibiotic-containing hydrogel wound dressing is therefore a promising treatment approach for severe abdominal trauma. Here an injectable, self-healing hydrogel composed of the gel-forming glycosaminoglycan oxidized chondroitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Since the gels were self-healable and responded quickly to the strain changes, we investigated whether our coacervate gels were also injectable. 5,[38][39][40] As shown in Fig. 4D, a rhodamine B dyed gel was prepared and put into a syringe, then we extruded it from needles with various diameters (20G -0.9 mm, 21G -0.8 mm and 26G -0.45 mm).…”
Section: Self-healing and Injectability Of Coacervate Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the gels were self-healable and responded quickly to the strain changes, we investigated whether our coacervate gels were also injectable. 5,[38][39][40] As shown in Fig. 4D, a rhodamine B dyed gel was prepared and put into a syringe, then we extruded it from needles with various diameters (20G -0.9 mm, 21G -0.8 mm and 26G -0.45 mm).…”
Section: Self-healing and Injectability Of Coacervate Gelsmentioning
confidence: 99%
“…Conventional coacervate hydrogels are rendered degradable because of their salt, pH or temperature responsiveness, however the degradation time can be exceedingly long under physiological conditions. 9,11,12,39,41 Previous work in our group on related pyridine-based polymeric systems has shown that (in addition to secondary amines) primary amines and thiols can be used to trigger deionization. 35,36 Treating our coacervate gels with two representative chemical signalsglycine (Gly, a primary amine) and sodium-3-mercaptopropane-sulfonate (SH-Na, a thiol), we indeed observed gel-sol transitions at a similar rate to that achieved with P (within 5 min).…”
Section: Accelerated Degradation Of Coacervate Gels In Cell Culture M...mentioning
confidence: 99%
“…In addition, due to the positive charge of PVA-SBQ, it has a certain promoting effect on cell adhesion and migration. 44,45 For wound healing, the hydrogel is a temporary scaffold for epidermal cell migration. Through vitro cell adhesion, we demonstrated that the PS 12 -OSA 1 -P 0.03 hydrogel could attract and attach a large number of living cells (Figure 3c).…”
Section: Biocompatibility Cell Migration and Adhesionmentioning
confidence: 99%
“…[10] Yang et al developed an injectable cationic hydrogel which exhibited a high binding capacity for proinflammatory molecules and thus reduced both local and systemic inflammation. [11] In our previous study, we have developed a size exclusive hydrogel resin functionalized with telodendrimer nanotrap (TD NT), which exhibits high binding affinity to LPS and pro-inflammatory cytokines with both charge and size selectivity. TD NT hydrogel resin has demonstrated 100% survival when combined with antibiotics in a severe sepsis mouse model.…”
Section: Doi: 101002/adtp202200127mentioning
confidence: 99%